Faktor-Faktor Yang Mempengaruhi Keterlambatan Deteksi Dini Kanker Serviks Pada Pasien Ca. Serviks: Factors Affecting Delay in Early Detection of Cervical Cancer in Patients Ca - Putri, Wina Octaviana Eka (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: Cervical cancer was the second most common cancer worldwide, accounting for 15% of all cancers in women. Every woman who had sexual intercourse had a risk of cervical cancer. Therefore, early detection needs to be done immediately. Methods: The research design used was cross-sectional. The technique used is purposive sampling with a total of 30. The instrument used is a question questionnaire regarding the IVA/Pap Smear examination, and internal factors (age, education, occupation, age at marriage, economic status, and parity) and external factors (health insurance, access to health services, husband's support, and level of knowledge). Results: The correlation between knowledge and IVA action obtained p-value = 0,013 < 0,05. Education p-value = 0,013 < 0,005; Age p-value = 0,552 > 0,05; Employment p-value = 0,450 > 0,05; Economic status p-value = 0,552 > 0,05; Age of Marriage obtained p-value = 0,553 > 0,05; Parity p-value = 0,488 > 0,05; Health Insurance p-value = 0,533 > 0,05; Health Services p-value = 0,395 > 0,05; and Husband's support obtained p-value = 0,000 < 0,05. Discussion: There was a significant relationship between internal factors, namely knowledge, and education, and external factors, namely the husband's support for patient decisions in conducting early detection of Ca cervical. It is hoped that these factors can be considered so that the delay in early detection in Ca cervical patients can be reduced.